Assessment of the feed additive consisting of Pediococcus acidilactici DSM 16243 for all animal species for the renewal of its authorisation (Lactosan GmbH & Co.KG). (19th July 2021) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Fašmon Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the assessment of the application for renewal of authorisation of Pediococcus acidilactici  DSM 16243 as a technological additive for all animal species. The applicant has provided evidence that the additive currently on the market complies with the existing conditions of authorisation. There is no evidence that would lead the FEEDAP Panel to reconsider its previous conclusions. Thus, the Panel concludes that the additive remains safe for all animal species, consumer and the environment under the authorised conditions of use. Regarding user safety Pediococcus acidilactici  DSM 16243 is not irritant to skin and eyes but is considered a skin and respiratory sensitiser. There is no need for assessing the efficacy of the additive in the context of the renewal of the authorisation.